The process of higher education in Peru. The decoloniality of university knowledge - Mejía Navarrete, Julio (2018)
The paper presents for its discussion some initial proposals on the development of the Peruvian university. The research is divided into four parts. The first section, studies the essential historical trends that define the current university. The second describes the influence of technological changes on university education. The third, shows the divergent relations between heterogeneity of knowledge and higher education mainly monocultural. The fourth part discusses the possibilities of the various university developments in Peru.